Development and validation of novel keloid-derived immortalized fibroblast cell lines - Sadiq, Alia; Khumalo, Nonhlanhla P.; Bayat, Ardeshir (Frontiers in Immunology, 2024)
Introduction: Keloids are a common connective tissue disorder with an ill-understood etiopathogenesis and no effective treatment. This is exacerbated due to absence of an animal model. Patient-derived primary keloid cells are insufficient as they age through passaging and have a limited supply. Therefore, there is an unmet need for development of a cellular model that can consistently represent keloid's pathognomic features.We developed keloid-derived immortalized fibroblast (KDIF) cell lines from primary keloid fibroblasts by transfecting the human telomerase reverse-transcriptase (hTERT) gene.Primary fibroblasts from keloid specific lesional (peripheral, middle and top) as well as extralesional sites were isolated and evaluated for cell line development and comparative cellular characteristics by employing qRT-PCR, Immunofluorescence staining. Moreover, the immortalized behaviour of KDIF cell lines was evaluated by comparing with cutaneous fibrosarcoma (FS), and dermatofibrosarcoma protuberans (DFSP) cell lines.Results: Stable KDIF cell lines with elevated expression of hTERT, exhibited the cellular characteristics of site-specific keloid fibroblasts. Histochemical staining for β-galactosidase, revealed significantly, lower number of β-gal positive cells in all three KDIF cell lines compared to primary keloid fibroblasts. The cell growth curve pattern studied over ten passages for all three KDIF cell lines and compared with control groups. Results showed that all three KDIF cell lines grew significantly faster and obtained a fast-growing characteristic as compared to primary keloid and normal fibroblasts. Phenotypic behavior in growth potential is an indicative of hTERT mediated immortalized transformation. Cell migration analysis revealed that top and middle KDIF cell lines exhibited similar migration trend as site specific primary keloid fibroblasts. Notably, peripheral KDIF cell line showed significantly enhanced cell migration in comparison to the primary peripheral fibroblasts. All KDIF cell lines expressed collagen 1 protein as keloid and fibrotic marker. Functional testing with Triamcinolone inhibited cell migration in KDIF. ATCC-STR profiling validated the KDIF as keloid representative cell line.Discussion: To our knowledge we provide the first novel Keloid-Derived Immortalized Fibroblast Cell Lines. These cell lines overcome the limitations related to primary cell passaging and tissue supply due to immortalized features and present an accessible and consistent experimental model for keloid research.